BUSINESS ANALYSIS A BOTTOM DRIFT GILL NET IN TANJUNG LAJAU VILAGE KUALA INDRAGIRI SUB-DISTRICT INDRAGIRI HILIR REGENCY RIAU PROVINCE - Lingga Saputra; Darwis Darwis; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT              This study attempts to analyze the capital, cost and feasibility of fisherman business bottom drift gill net. fisherman developing the fishing industry in the Village Tanjung Lajau Kuala Indragiri Subdistrict, Indragiri Hilir Regency Riau Province. The reseach result show the total investment invested by fishermen in the business ranges from IDR155,918,000 to IDR 165,937,700 with an average of IDR 157,985,500. The total cost of the net in doing business ranges from IDR.120.269.000 to IDR. 128,237,000 with an average of IDR123,217,820. Average net income of fishermen bottom drift gill net from per trip that is equal to IDR. 2.027.000. Average net income of bottom drift gill net per year in doing business ranges from IDR. 57.119.236  to IDR. 126.498.443  with an average of IDR.93.949.180.Whose average score BCR 1,76, value FRR 59,42% and value PPC 1,8 years. An analysis of them show bottom drift gill nets business this worth to be developed again Keyword: bottom drift gill net, business analyze, cost, income